Assessing the quality of water used by the community of Madlangamphisi in the Hhohho region of Eswatini - Dlamini, M. V.; Manyatsi, A. M.; Dlamini, K. A. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Clean water is necessary for communities. However, in some communities water is obtained from various sources which potentially can cause a health hazard. The research was conducted to assess the quality of domestic water used by the community of Madlangamphisi area in the Hhohho district of Eswatini. A questionnaire and physical water sampling were used to collect both the qualitative and quantitative data reported in this paper. Water samples to determine the quality of water used for domestic purposes in the area were taken from the common sources, the community borehole and the Nkomazi river. The samples were tested for microbial water quality and the Eswatini Water Services Corporation drinking water guidelines used as the bench mark. A total of 169 households out of 300 households were randomly selected to participate in the survey. The majority (51.5%) of the households used water from the river, 24.9% used water from the borehole, 18.3% depended on rainfall and 5.3% used water from seasonal streams. Water analysis results revealed that water from the river was polluted, as it contained 8/100 ml of faecal coliforms (E. coli) which was higher than 0/100 ml recommended in the benchmark. The water from the borehole did not contain E. coli. The majority (56.2%) of the households did not purify the water before use, 27.2% added bleach, 12.4% used boiling and 4.1% used treatment sachets for purifying the water. The study concluded that Madlangamphisi community faced a serious risk of water borne diseasese specially faecal coliforms (E. coli).The study observed that there is a need to introduce a rural water supply scheme in the area to solve the water quality problemsto avoid a potential outbreak of diseases.